Wireless LAN access network architecture for mobile operators. - Ala-Laurila, J. (IEEE Communications magazine)
The evolution of IP-based office applications has created a strong demand for public wireless broadband access technology offering capacity far beyond current cellular systems. Wireless LAN access technology provides a perfect broadband complement for the operators' existing GSM and GPRS services in an indoor environment. Most commercial public wireless LAN solutions have only modest authentication and roaming capability compared to traditional cellular networks. This article describes a new wireless LAN system architecture that combines the WLAN radio access technology with mobile operators' SIM-based subscriber management functions and roaming infrastructure. In the defined system the WLAN access is authenticated and charged using GSM SIM. This solution supports roaming between cellular and WLAN access networks and is the first step toward an all-IP network architecture. The proto-type has been implemented and publicly verified in a real mobile operator network